State of the art in the aeroelasticity of wind turbine blades: Aeroelastic modelling. (October 2016) - Wang, Lin; Liu, Xiongwei; Kolios, Athanasios
Abstract: With the continuous increasing size and flexibility of large wind turbine blades, aeroelasticity has been becoming a significant subject for wind turbine blade design. There have been some examples of commercially developed wind turbines experiencing aeroelastic instability problems in the last decade, which spokes for the necessity of aeroelastic modelling of wind turbine blades. This paper presents the state-of-the-art aeroelastic modelling of wind turbine blades, provides a comprehensive review on the available models for aerodynamic, structural and cross-sectional analysis, discusses the advantages and disadvantages of these models, and outlines the current implementations in this field. This paper is written for both researchers new to this research field by summarising underlying theory whilst presenting a comprehensive review on the latest studies, and experts in this research field by providing a comprehensive list of relevant references in which the details of modelling approaches can be obtained.